Oocyte vitrification in female cancer patients - Dalvit, Gabriel (2018)
The increase in the use of oocyte cryopreservation occurred after the introduction of the vitrification technique and the birth of the first baby with this method in 1999. Using this powerful tool, scientists have helped women to cryopreserve their gametes by oocyte or ovarian cortex vitrification. For a decade, important advances in vitrification technology have improved clinical efficiency and results. This progress has reduced the dependence on the operator skill and has increased the success rate to high and homogeneous levels. As a result, vitrification has become reliable and the current trend shows a definite increase in its use compared to slow freezing. The new and advanced method known as “Cryotech method” ensures achievement of 100% viability in oocytes and embryos at any stage. The technique is set to make definite changes in the procedure of cryopreservation in the whole world. Due to the great emotional effect caused by cancer diagnosis and the need for immediate treatment, the potential gonadotoxic effects of cancer or its treatment are not normally discussed at the time of diagnosis. Fertility preservation is a recent effort, and many cancer patients and health workers are not familiar with its rapid development on research and on implementation in clinical practice. Some techniques of fertility preservation as oocyte or ovarian cortex vitrification have been validated in the past 5 years with healthy children born without fertility treatment, even when these continue to be experimental cases. Combining all the knowledge we now have on oocytes and ovarian cortex vitrification with hormonal stimulation of the ovary even in the luteal phase and the effectiveness of the process of assisted reproduction, we can say that it is possible to preserve reproductive lives of patients with cancer even in pediatric patients.